2020
DOI: 10.1002/ps.5806
|View full text |Cite
|
Sign up to set email alerts
|

Realized heritability, inheritance and cross‐resistance patterns in imidacloprid‐resistant strain of Dysdercus koenigii (Fabricius) (Hemiptera: Pyrrhocoridae)

Abstract: BACKGROUNDImidacloprid, a neonicotinoid insecticide, is widely sprayed alone or mixed with other insecticides against Dysdercus koenigii, a potential pest of cotton in Pakistan. Recently, resistance to imidacloprid in field populations of D. koenigii has developed because of its overuse. Herein, we have investigated inheritance of imidacloprid resistance in D. koenigii and its cross‐resistance to other insecticides.RESULTSThe imidacloprid‐selected population had a 91 421‐fold increase in resistance to imidaclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 54 publications
1
9
2
Order By: Relevance
“…comm.). Similar to our results, higher resistance levels have previously been reported following laboratory selections in DCB to chlorfenapyr (RR = 149.07‐fold), imidacloprid (RR = 104‐fold), 41,50 N. lugens to sulfoxaflor (RR =123.6‐fold), 42 P. solenopsis to acetamiprid (RR = 315‐fold) 81 and Dysdercus koenigii (Fabricius) to imidacloprid and emamectin benzoate 82,83 . However, the results of this study show that DCB has strong potential for the development of resistance to sulfoxaflor in the field (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…comm.). Similar to our results, higher resistance levels have previously been reported following laboratory selections in DCB to chlorfenapyr (RR = 149.07‐fold), imidacloprid (RR = 104‐fold), 41,50 N. lugens to sulfoxaflor (RR =123.6‐fold), 42 P. solenopsis to acetamiprid (RR = 315‐fold) 81 and Dysdercus koenigii (Fabricius) to imidacloprid and emamectin benzoate 82,83 . However, the results of this study show that DCB has strong potential for the development of resistance to sulfoxaflor in the field (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…In the current study, the nonsignificant difference in LC 50 values of F 1 and F 1 ' reciprocal crosses among resistant and susceptible populations revealed that no maternal effects were involved in controlling sulfoxaflor resistance in selected populations of DCB, rather its mode of inheritance was autosomal. The autosomal mode of resistance inheritance has also been reported in different insects to various insecticides like O. hyalinipennis to imidacloprid 41 and chlorfenapyr, 50 D. koenigii to imidacloprid and emamectin benzoate, 82,83 and M. domestica to fipronil 84 . However, in contrast to the present results, sex‐linked inheritance of lambda‐cyhalothrin resistance in Tetranychus urticae (Koch) (laboratory selected) has been reported 85 …”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Higher phenotypic variance may come from gene mutations and laboratory selection pressure, but in field environments it may come from migration of individuals, insecticide alternation, and ecological factors [ 23 , 25 , 26 ]. The h 2 estimation is a useful variable in proactive and effective resistance management of insect pests [ 27 , 28 ]. The h 2 estimation of resistance through laboratory selection predicts the rate of phenotypic and genetic variations due to insecticide resistance [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overuse of insecticides has also resulted in environmental pollution, increased the cost of preventive control, and caused destruction of non-target organisms [12,13]. These issues emphasize the necessity to employ an integrated pest management program against insect pests, including the house fly [14][15][16]. To overcome the development of resistance, excessive applications of insecticides at increasing dose rates and more frequent intervals have been used, but these practices have escalated the problem and rendered the control of house fly even more difficult all over the world, particularly in areas where most suitable insecticides have lost their efficacy [17].…”
Section: Introductionmentioning
confidence: 99%